2017
DOI: 10.1021/acssuschemeng.6b02458
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Thermo-Mechanical Properties of Poly(lactic acid)/Lignin-Coated Cellulose Nanocrystal Composites

Abstract: Improving the processability and physical properties of sustainable biobased polymers using biobased fillers is essential to preserve its biodegradability and make them suitable for different end user applications. Herein, we report the use of spray-dried lignin-coated cellulose nanocrystals (L-CNCs), a biobased filler, to modify the rheological and thermo-mechanical properties of poly­(lactic acid) (PLA) composites. The lignin coating on CNCs not only improved the dispersion of CNCs but also enhanced their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 53 publications
(75 reference statements)
5
96
0
Order By: Relevance
“…Crystallites from the CNCs distributed in the PLA matrix formed impermeable regions; this created a more tortuous diffusion path for permeants and led to a slower diffusion process . Additionally, several studies showed that the CNCs also act as a nucleating agent to induce crystallization; this results in a higher degree of crystallinity . This finding was corroborated by the data listed in Table and clearly indicated that the degree of crystallinity of PLA increased with CNC content.…”
Section: Resultsmentioning
confidence: 55%
“…Crystallites from the CNCs distributed in the PLA matrix formed impermeable regions; this created a more tortuous diffusion path for permeants and led to a slower diffusion process . Additionally, several studies showed that the CNCs also act as a nucleating agent to induce crystallization; this results in a higher degree of crystallinity . This finding was corroborated by the data listed in Table and clearly indicated that the degree of crystallinity of PLA increased with CNC content.…”
Section: Resultsmentioning
confidence: 55%
“…The Takayanagi model is so close to the experimental values by considering E 0 = 2.5 GPa and E 1 = 1,054 GPa. The modulus values shown by composites are greater than the theoretical values because of higher reinforcement effect of MWCNT . This is more visible in composite with 2 wt% MWCNT.…”
Section: Resultsmentioning
confidence: 78%
“…Rheology is a powerful technique to study the microstructure of polymer blends from the variation of melt viscosity and storage modulus [52]. The rheological behavior of neat PLLA, PLLA/VUB binary and PLLA/VUB/ PDLA ternary blends was studied by rotational rheometer at 190°C under frequency-sweep mode from 0.01 to 100 Hz.…”
Section: Rheological Behaviormentioning
confidence: 99%